Orbitocranial Penetrating Injury With Multiple Vessel Invasion in an Infant: A Case Report and Literature Review - Wu, Yun; Chen, Tiange; Yuan, Meng; Mzimbiri, Juma Magogo; Liu, Ziyuan; Chen, Yilei; Luo, Xiangying; Chen, Fenghua; Liu, Jinfang (Frontiers in Neurology, 2020)
Orbitocranial penetrating injury (OPI) with multiple vascular invasions is a rare occurrence. To our knowledge, experience with its clinical treatment is rather limited, especially for infants. This case report describes an infant who fell from a 0.5 m high bed and landed on a toy with a keen-edged plastic rod. The fractured end of the rod was noted at the medial aspect of the left eyelid, and she was experiencing impaired consciousness. Computed tomography showed that the foreign body penetrated the cavernous sinus with internal carotid artery involvement, and compressed the transverse sinus through the cerebellum. Emergency surgery was performed with temporal occlusion of the left common carotid artery. The rod was removed from the orbital side, and bleeding from cavernous sinus region was effectively controlled under direct inspection via a sub-temporal approach. The patient was successfully treated and recovered consciousness after 17 days. This is the first report of successful management of OPI combined with multiple vascular injury in an infant. Herein, we highlight the anatomical imaging features of the injuries and also the individualized strategy concerning vascular invasion.